Strategi Akselerasi Ekonomi Desa : Penguatan Literasi Keuangan Digital dan Branding Lokasi Usaha UMKM di Desa Battu Winangun - Santosa, Junjung Rahmat; Serli Alkifti; Sevti Anggraini; Gitta Destalya Adrian Nova (Jurnal Inovasi Pengabdian Masyarakat, 2026)
Optimizing the digital economy is a strategic step to enhance the competitiveness of rural MSMEs. In Battu Winangun Village, Ogan Komering Ulu Regency, MSMEs face challenges such as reliance on cash transactions, low digital financial literacy, and a lack of online visibility. This community service aims to optimize the digital economy through the implementation of the Quick Response Code Indonesian Standard (QRIS) and business location digitalization. The method employed is Asset-Based Community Development (ABCD), involving observation, socialization, and technical assistance. The results demonstrate an increase in digital literacy, with five MSMEs successfully adopting QRIS and registering their locations on digital maps. This implementation has improved transaction efficiency, financial recording, as well as business visibility and accessibility. This program is expected to accelerate an inclusive and sustainable rural digital economic transformation.